SIMULTANEOUS INFRARENAL AORTIC PROSTHESIS IMPLANTATION AND RENAL TRANSPLANTATION IN PATIENT ON PERITONEAL DIALYSIS - A. V. Kolsanov; M. S. Mikhaylov; B. I. Yaremin; D. A. Chernovalov; A. A. Mironov (Вестник трансплантологии и искусственных органов)
SIMULTANEOUS INFRARENAL AORTIC PROSTHESIS IMPLANTATION AND RENAL TRANSPLANTATION IN PATIENT ON PERITONEAL DIALYSIS